Constitutional rationality and process guarantees - Chiarloni, Sergio (2016)
Constitutional rationality dictates that procedural safeguards will be balanced in order to consider the interests of both parties that in this case are opposed in a controversy. The concept of rationality is analized by the author as a value that goes beyond the scope of the legal right, that is, as a constitutive element of the homo sapiens. This is the reason why the conviction is spread among constitutionalists and legal philosophers  that the principle of practical rationality has assumed the rank of constitutional value because of the constitutionalization of human rights. All of this is explained in the prospective of the civil process, where the constituent has instituted the guarantee of the appeal in order to guarantee equality in the treatment for the procedural parties.